Functional characterization of novel MFSD8 pathogenic variants anticipates neurological involvement in juvenile isolated maculopathy. Issue 3 (12th December 2019) - Bauwens, Miriam; Storch, Stephan; Weisschuh, Nicole; Ceuterick‐de Groote, Chantal; De Rycke, Riet; Guillemyn, Brecht; De Jaegere, Sarah; Coppieters, Frauke; Van Coster, Rudy; Leroy, Bart P.; De Baere, Elfride
Abstract: Biallelic MFSD8 variants are an established cause of severe late‐infantile subtype of neuronal ceroid lipofuscinosis (v‐LINCL), a severe lysosomal storage disorder, but have also been associated with nonsyndromic adult‐onset maculopathy. Here, we functionally characterized two novel MFSD8 variants found in a child with juvenile isolated maculopathy, in order to establish a refined prognosis. ABCA4 locus resequencing was followed by the analysis of other inherited retinal disease genes by whole exome sequencing (WES). Minigene assays and cDNA sequencing were used to assess the effect of a novel MFSD8 splice variant. MFSD8 expression was quantified with qPCR and overexpression studies were analyzed by immunoblotting. Transmission electron microscopy (TEM) was performed on a skin biopsy and ophthalmological and neurological re‐examinations were conducted. WES revealed two novel MFSD8 variants: c.[590del];[439+3A>C] p.[Gly197Valfs*2];[Ile67Glufs*3]. Characterization of the c.439+3A>C variant via splice assays showed exon‐skipping (p.Ile67Glufs*3), while overexpression studies of the corresponding protein indicated expression of a truncated polypeptide. In addition, a significantly reduced MFSD8 RNA expression was noted in patient's lymphocytes. TEM of a skin biopsy revealed typical v‐LINCL lipopigment inclusions while neurological imaging of the proband displayed subtle cerebellar atrophy. Functional characterization demonstrated the pathogenicity of two novel MFSD8 variants, found in a child with an initial diagnosis of juvenile isolated maculopathy but likely evolving to v‐LINCL with a protracted disease course. Our study allowed a refined neurological prognosis in the proband and expands the natural history of MFSD8 ‐associated disease. Abstract :